2003
DOI: 10.1001/jama.289.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Community Knowledge of the Warning Signs and Risk Factors for Stroke

Abstract: ContextPoor public knowledge of stroke warning signs and risk factors limits effective stroke intervention and prevention.Objective To examine temporal trends in public knowledge of stroke warning signs and risk factors. Design and SettingPopulation-based random-digit telephone survey conducted in July-November 2000 among individuals in the greater Cincinnati, Ohio, region.Participants A total of 2173 survey respondents (69% response rate) were randomly identified based on their demographic similarities to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
303
8
25

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(362 citation statements)
references
References 27 publications
26
303
8
25
Order By: Relevance
“…7,8,14Á17 For the sake of brevity, we designed our survey to use level of education as a single indicator of SEP. We did not intend to make comparisons between Female gender has been previously shown to be predictive of increased stroke knowledge. 7,8,14,15,18 This finding was suggested by our univariate analysis (p 00.031); however, multivariate analysis was not able to confirm this association with the same level of statistical significance (p 00.057). This is likely a type II statistical error, which might have been overcome by increasing our sample size to boost the statistical power of our test.…”
Section: Discussion/conclusionmentioning
confidence: 65%
See 1 more Smart Citation
“…7,8,14Á17 For the sake of brevity, we designed our survey to use level of education as a single indicator of SEP. We did not intend to make comparisons between Female gender has been previously shown to be predictive of increased stroke knowledge. 7,8,14,15,18 This finding was suggested by our univariate analysis (p 00.031); however, multivariate analysis was not able to confirm this association with the same level of statistical significance (p 00.057). This is likely a type II statistical error, which might have been overcome by increasing our sample size to boost the statistical power of our test.…”
Section: Discussion/conclusionmentioning
confidence: 65%
“…Studies reporting data for multiple age categories have shown that stroke knowledge appears to be at its peak during the middle years of life, 17 while those using a single age cut-off of 65 to 75 years old have shown the elderly to have decreased stroke knowledge. 9,14,18 Note: Comparison of stroke knowledge by gender and use of primary care physician was performed using a t-test, while comparison by level of education and by number of self-reported risk factors were performed using ANOVA and Scheffé post-hoc analysis. *Level of education was related to ability to correctly identify stroke warning signs (F 04.87; df 03241; p 00.003); Scheffé post-hoc analysis revealed that mean knowledge score for category 'four or more years of college' was significantly different from the 'high school or GED' category (p 00.035).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…[3][4][5] Studies of stroke-related knowledge have primarily focused on warning signs and risk factors. 6,7 At least 3 telephone-based surveys have included questions about awareness of tPA treatment for stroke, and their results have varied widely. In a 1999 study conducted in Corpus Christi, Tex, 48% of Hispanics and 57% of non-Hispanic whites were aware that a treatment for acute stroke existed, and 38% and 62%, respectively, were aware that there was a time window for stroke treatment.…”
Section: S Troke Is the Third Leading Cause Of Death In The Unitedmentioning
confidence: 99%
“…Despite television being the most frequently cited source of health information by the general public, 77 Pribble and colleagues 78 found that few health stories about stroke were reported on local television news programs. No known studies, to date, have documented the use of television as a media for conveying health information about aphasia.…”
mentioning
confidence: 99%